Tingkat Keramahan Lingkungan Alat Tangkap Bubu Lipat di Kelompok Nelayan Sakera Desa Kramat Kecamatan Kraton Kabupaten Pasuruan Jawa Timur - Karimatun Nisak; M. Tajuddin Noor; Exist Saraswati (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
Fishermen in Kramat Village are traditional fishermen who use small boats and simple fishing gear, one of which is folding bubu fishing gear. This research was carried out in the Sakera fishermen group located in Kramat Village, Kraton District, Pasuruan Regency in October-December 2024. The purpose and benefits of this study are to find out and evaluate the level of environmental friendliness of folding bubu fishing gear in the Mangrove crab catching process and to find out the composition of the catch of folding bubu fishing gear. in the Sakera fishermen group This study uses survey methods, direct observation and interviews. The analysis of the level of environmental friendliness includes 9 criteria of the Code of Conduct for Responsible Fisheries (CCRF). The results of the calculation of the environmental cleanliness score obtained a score of 30.78 which means that the folding bubu fishing gear in the Sakera fishermen group is very environmentally friendly. The catch was obtained 3 main types of fish.